1979
DOI: 10.3171/jns.1979.51.2.0147
|View full text |Cite
|
Sign up to set email alerts
|

Management of extracranial carotid stenosis and intracranial aneurysms

Abstract: Twenty patients with extracranial carotid stenosis and intracranial aneurysms are reviewed. Fifteen of these patients had transient ischemic attacks (TIA's) and incidental aneurysms. The other five presented with symptoms referrable to an aneurysm, and angiography revealed significant carotid stenosis. None of the patients who presented with TIA's and underwent endarterectomy suffered subarachnoid hemorrhage. However, those patients who presented with symptoms referrable to an aneurysm and underwent endarterec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The only death was reported by Adams [2], whose patient underwent a left endarterectomy and 7 months later died from the rupture of a 10 mm posterior communicating artery aneurysm. Stern et al [26] concluded that carotid endarterectomy is unlikely to provoke aneurysmal bleeding in the peri-operative period. Nevertheless, the correction of a severe stenosis generally causes a marked increase in blood flow distally to the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only death was reported by Adams [2], whose patient underwent a left endarterectomy and 7 months later died from the rupture of a 10 mm posterior communicating artery aneurysm. Stern et al [26] concluded that carotid endarterectomy is unlikely to provoke aneurysmal bleeding in the peri-operative period. Nevertheless, the correction of a severe stenosis generally causes a marked increase in blood flow distally to the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of cerebral angiography to evaluate patients for cerebral ischaemia has shown an incidence of coincidental aneurysms ranging from 2.8% to 5% [3,20,22,24,25]. Until the mid eighties, most authors reported good results by first operating on the stenosis and leaving the aneurysm untreated [2,5,11,20,24,26]. Indeed, the correction of a severe extracranial stenosis of the internal carotid artery (ICA) might increase flow, pressure and turbulence in the aneurysmal sac located on the same side or in the anterior circle of Willis complex, with a greater possibility of aneurysm enlargement and rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported on the stability of small unruptured aneurysms after stenting or endarterectomy (Ladowski et al, 1984;Stern et al, 1979;Suh et al, 2011). These studies, however, do not describe with any uniformity the dimensions of the aneurysms (some studies describe aneurysms as large as 4 mm or 7 mm) or the treatments employed to control hypertension and to achieve hemodynamic stability; furthermore, the periods of observation are short.…”
Section: The Association Of Carotid Stenosis With Cerebral Aneurysmsmentioning
confidence: 99%
“…Because only 3 to 5% of the patients have both lesions (Kappelle et al, 2000;Suh et al, 2011), 2,000 to 3,334 cases must be included to reach the statistically significant number of approximately 100 cases in which patients have both carotid artery stenosis and a cerebral aneurysm. Stern et al (1979) reported on one case of a fatal rupture of a cerebral aneurysm after EAC. They suggested that the risk of subarachnoid hemorrhage during endarterectomy might be increased in patients with aneurysms (Stern et al, 1979).…”
Section: The Association Of Carotid Stenosis With Cerebral Aneurysmsmentioning
confidence: 99%
See 1 more Smart Citation